Supply Chain of Potato in East Khasi Hills District of Meghalaya: A temporal Analysis - Rajavardhan, M.; Sethi, B.; Singh, Ram (Indian Journal of Extension Education, 2020)
Potato crop in the state has its own recognition and it is reaching to every ranch of the state. Keeping in view the present study was conducted in East Khasi hills district of the Meghalaya state. The findings demonstrates the growth trends of potato crop, producers’ surplus, disposal pattern, price spread which are immense for developing the policy on production and post harvest management of the crop. As the channel-I was preferred and maximum produce was disposed; the channel-I need to be strengthened through technological intervention like value addition in the crop. Further, the price spread analysis is an insight for improvement in the market for unscrupulous practices adopted by different intermediaries in the potato market.
Keywords: Channel; Potato; Supply; Value addition